Joint or Independent? Sourcing and Inspection Decisions in Emerging Economies - Chen, Jiguang; Wu, Xiaole (Production and Operations Management, 2026)
In the presence of supplier quality risk, offering suppliers a higher procurement price or increasing inspection effort are two approaches to motivate a supplier to invest in higher quality. In this paper, we consider three sourcing and inspection strategies for a brand with two branch shops facing supplier quality risk: joint, mixed, and independent strategies. Under the joint strategy, the brand jointly sources for its two shops by offering a uniform procurement price and inspects both shops in a centralized way (joint sourcing and joint inspection). Under the mixed strategy, the brand jointly sources for its two shops by offering a procurement price, and then each shop decides its own inspection probability (joint sourcing and independent inspection). Under the independent strategy, each shop decides its own procurement price and inspection probability (independent sourcing and independent inspection). We find that among the three strategies, the joint strategy mostly relies on the inspection tool to motivate suppliers’ high-quality effort, and the mixed strategy mainly utilizes the procurement price tool by offering the highest price for suppliers’ high quality. We further find that, no matter whether the brand is purely profit-driven or cares about the quantity of low-quality products sold to the market, the mixed strategy is always preferred to the independent strategy. The preference between mixed and joint strategies is jointly determined by the fixed cost incurred in joint sourcing and inspection accuracy. For intermediate fixed cost, if the inspection accuracy is sufficiently high, the mixed strategy is preferred to the joint strategy; otherwise, the joint strategy is preferred to the mixed strategy. Interestingly, when a brand becomes more socially responsible (i.e., it cares more about the quantity of low-quality products sold to the market), it may switch from a reliable supplier to a risky supplier, leading to more low-quality products being sold to the market. This is because with a greater level of social responsibility, the brand’s higher inspection efforts become more credible, which motivates the risky supplier’s higher quality effort.